Pure red cell aplasia and seronegative myasthenia gravis in association with thymoma - Sun Yong Lee; Amandeep Gill; Syung Min Jung (Greater Baltimore Medical Center, 2020)
Pure red cell aplasia is an uncommon paraneoplastic syndrome of thymoma. Myasthenia gravis is the most common paraneoplastic syndrome associated with thymoma. We present a case of a 79-year-old Pacific Islander female who presented with profound fatigue, generalized weakness, significant unintentional weight loss, bilateral ptosis, and anemia. The bone marrow biopsy showed near absence of erythroid elements consistent with pure red cell aplasia. Ice-pack test was consistent with myasthenia gravis and computed tomography of the chest demonstrated a thymoma. The patient was started on immunosuppressive treatment with prednisone and cyclosporine. This case demonstrates a rare combination of paraneoplastic manifestations of thymoma: pure red cell aplasia and myasthenia gravis.